Science and Pseudoscience : A Conversation with Michael Gordin. - Burton, Howard (Ideas Roadshow conversations., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Michael Gordin, Rosengarten Professor of Modern and Contemporary History at Princeton University. This thought-provoking, extensive conversation examines the strange case of Immanuel Velikovsky, author of the bestselling book ""Worlds in Collision"" that managed to provocatively combine unbridled scientific speculation with ancient myth, as a way of probing the often-problematic boundary between science and pseudoscience.By all accounts, Velikovsky was a decidedly curious character. The notorious Russian-born docto.